Identification of BRCA1:c.5470_5477del as a Founder Mutation in Chinese Ovarian Cancer Patients - Li, Jun; Han, Sile; Zhang, Cuiyun; Luo, Yanlin; Wang, Li; Wang, Ping; Wang, Yi; Xia, Qingxin; Wang, Xiaoyan; Wei, Bing; Ma, Jie; Li, Hongle; et al. (Frontiers in Oncology, 2021)
Predisposition of germline BRCA1/2 mutations (gBRCAMUT) increases the risk of breast and ovarian cancer in females, but the mutation prevalence and spectrum are highly ethnicity-specific with different recurrent mutations being reported in different populations. Hereby, we performed hybridization-based target sequencing of BRCA1/2 in 530 ovarian cancer patients from Henan, the central region of China, followed by haplotype analysis of six short tandem repeat (STR) markers in the patients with recurrent mutations to determine their founder effect. About 28.3% (150/530) of the OC patients in our cohort harbored gBRCAMUT; of the 151 mutations, 117 in BRCA1 and 34 in BRCA2, identified in this study, BRCA1:c.5470_5477del, c.981_982del, and c.4065_4068del are the top three mutants, recurrently detected in eight, seven, and six independent patients respectively. Haplotype analysis identified a region of 0.6 MB genomic length covering BRCA1 highly conserved across all eight carriers of BRCA1:c.5470_5477del, but not c.981_982del, suggesting a consequence of founder effect. Retrospective analysis in a subgroup of serous ovarian cancer patients revealed gBRCAMUT status was not associated with the progression-free survival (PFS); instead, an expression of Ki-67% ≥50% was associated with a shorter PFS (p = 0.041). In conclusion, patients with pathogenic or likely pathogenic gBRCAMUT account for 28.3% of the OC cases from Henan, and BRCA1:c.5470_5477del, the most frequently detected mutation in Henan patients, is a founder mutation in the population.